CSF 7‐ketocholesterol is related to β‐amyloid and white matter microstructure in healthy adults: Neuroimaging / Normal brain aging. (7th December 2020) - Iriondo, Ane; Garcia‐Sebastian, Maite; Arrospide, Arantzazu; Arriba, Maria; Aurtenetxe, Sara; Barandiaran, Myriam; Clerigue, Montserrat; Ecay, Mirian; Estanga, Ainara; Gabilondo, Alazne; Izagirre, Andrea; Saldias, Jon; et al.
Abstract: Background: Abnormal cholesterol metabolism changes the neuronal membrane and interferes with amyloidogenesis. Oxysterols in CSF are related to Alzheimer's disease (AD) biomarkers in mild cognitive impairment and dementia. Cholesterol turnover is important for axonal and white matter (WM) microstructure maintenance. We aim to demonstrate that the association of oxysterols, biomarkers and WM microstructure occurs early in asymptomatic individuals. Method: We studied the association of inter‐individual variability of CSF 24‐hydroxycholesterol (24‐OHC), 27‐hydroxycholesterol (27‐OHC), 7‐ketocholesterol (7‐KC), 7β‐hydroxycholesterol (7β‐OHC), β‐amyloid1‐42 (Aβ42 ), total‐tau (t‐tau), phosphorylated‐tau (p‐tau), neurofilament (NfL) and WM microstructure in cognitive regions, using diffusion tensor imaging (DTI), generalized lineal models and moderation/mediation analyses in 153 healthy adults. Result: 7‐KC levels were related to Aβ42 ( B = ‐1.41; p = 0.041). Higher 7‐KC levels were related to lower fractional anisotropy (FA) and higher mean (MD), axial (AxD) and radial (RD) diffusivity in cognitive regions. 7‐KC modulated the association between AxD and NfL in the corpus callosum splenium ( B = 39.39, p = 0.017) and genu ( B = 68.64, p = 0.000) and fornix ( B = 10.97, p = 0.000). Lower Aβ42 levels were associated to lower FA and higher MD, AxD and RD in the fornix, corpus callosum, inferior longitudinal fasciculus and hippocampus. The association between AxD and Aβ42 was moderated by 7K‐C (p= 0.048). Conclusion: This study adds clinical evidence to support the role of 7K‐C on axonal integrity and the involvement of cholesterol metabolism in the Aβ42 generation process.